In Vitro Hepatic Metabolism of Curcumin Diethyl Disuccinate by Liver S9 from Different Animal Species - Jithavech, Ponsiree; Ratnatilaka Na Bhuket, Pahweenvaj; Supasena, Wiwat; Qiu, Guanyinsheng; Ye, Shengqing; Wu, Jie; Wong, Tin Wui; Rojsitthisak, Pornchai (Frontiers in Pharmacology, 2020)
The liver S9 (LS9) represents a nearly complete collection of all hepatic drug metabolizing enzymes. It is a low-cost model with better drug metabolic activity prediction than microsomes and human hepatocytes for drug metabolic activity prediction. This study aims to identify suitability of using LS9 in drug metabolism profiling as a function of animal sources of enzymes with respect to possible translation of in vitro outcome to clinical study. In vitro hepatic metabolism of curcumin diethyl disuccinate (CDD), in LS9 of rat, dog, monkey, and human, was evaluated. The identity of CDD metabolites, and their metabolism kinetic parameters, including degradation rate constants, in vitro/in vivo intrinsic clearances, and half-lives were determined. CDD was rapidly metabolized into monoethylsuccinyl curcumin and curcumin in LS9 of all tested species mainly by carboxylesterases (CESs), including CES1 and CES2, and butyrylcholinesterase. The in vitro intrinsic clearance of CDD progressed in the following order: human > dog > monkey > rat, whereas monoethylsuccinyl curcumin in the order of dog > monkey > human > rat of which was not correlated to in vivo clearance of CDD and monoethylsuccinyl curcumin where dog > monkey > rat > human. In vitro drug metabolism data inferred from LS9 of non-human origin especially monkey and dog origin cannot be implied as preclinical data for human trials, where human is characterized by a smaller liver to body weight than monkey, dog and rat. In vivo drug metabolism is dictated by the anatomical factor of the test subject.